The Effect of ISAK 35 implementation, Organizational Culture and Gender on the Quality of Financial Reports - Octaviani, Clara; Fahmi, Muhammad; Azmi, Ika Nur (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Accounting is a system used in the process of recording and reporting the financial statements of an entity, both profit-oriented entities and non-profit entities. Basically, non-profit entities are different from business entities. Because student organizations are non-profit entities, in which the Financial Accounting Standards Statement (PSAK) 45.2019 which was later replaced by the Interpretation of Financial Accounting Standards (ISAK) 35 regulates the presentation and financial reporting of non-profit entities, non-profit organizations prepare their financial statements in accordance with applicable standards. The purpose of making financial statements in accordance with ISAK 35 is to provide information on the financial position, financial performance and cash flow of the entity that is useful for most users of financial statements in making economic decisions. By conducting this study, we want to show how much influence the implementation of ISAK 35, organizational culture and gender have on the quality of financial statements of student organizations at Universitas Tanjungpura.